Construction Workers' Issues From Worldwide and Saudi Arabia Studies - Al-Emad, Nashwan (International Journal of Sustainable Construction Engineering and Technology, 2021)
Most of the construction workers in Saudi Arabia are foreigners from several countries such as Pakistan, Bangladesh and others. These foreign workers are facing challenges not only regarding the construction demanding tasks but also facing social and climate adaptions. This review paper compiles previous research works related to construction workers which were carried out worldwide including Saudi Arabia. It able to extract 63 issues from worldwide studies and narrowed it to 45 issues for Saudi Arabia. With the issues from Saudi Arabia, it was clustered into 2 main categories which are technical and non-technical related issues. In technical category, 15 issues were assigned to 4 groups while for non-technical category, 30 issues were assigned to 7 groups. Based on frequency analysis the 3 most frequent construction workers' issues from worldwide studies are shortage of skilled labours, low productivity level and lack of experience. While from Saudi Arabia studies the 3 most frequent construction workers' issues for both technical and non-technical groups are shortage of skilled labours, low productivity level, unqualified workforce and personal conflicts among labours, absenteeism of labours, discrimination based on nationality respectively. These preliminary findings serve as a basis for further investigation related to construction workers in Saudi Arabia.